1997
DOI: 10.1034/j.1399-3054.1997.1010117.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological responses of Fagus sylvatica seedlings to changing light conditions. II. The interaction of light environment and soil fertility on seedling physiology

Abstract: M. 1997. Ecophysiological responses of Eagus sylvatica seedlings to changing light conditions. II. The interaction of light environment and soil fertility on seedling physiology. -Physiol. Plant. 101: 124-134.The survival and growth of natural beech regeneration after canopy removal is variable and little is known about ecophysiological mechanisms of these responses. Biomass, nonstructural carbohydrate levels and nitrogen concentrations were measured in an Italian population of European beech seedlings. Seedli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 14 publications
(24 reference statements)
4
21
1
1
Order By: Relevance
“…Consequently, area based values of antioxidants and photoprotective pigments are of potential importance, to relate defense capacity to environmental impacts [46], especially when tree ageing coincides with alterations in leaf morphology [39,46,47]. In coincidence with previous studies in seedling and adult Fagus sylvatica trees [12,15,20,22,26,29,30,41] there were clear differences in antioxidant and pigment contents with respect to crown position. The higher dry weight and area based contents of ascorbate and a-tocopherol in sun exposed leaves are consistent with their greater need for antioxidant protection [10].…”
Section: Discussionsupporting
confidence: 64%
“…Consequently, area based values of antioxidants and photoprotective pigments are of potential importance, to relate defense capacity to environmental impacts [46], especially when tree ageing coincides with alterations in leaf morphology [39,46,47]. In coincidence with previous studies in seedling and adult Fagus sylvatica trees [12,15,20,22,26,29,30,41] there were clear differences in antioxidant and pigment contents with respect to crown position. The higher dry weight and area based contents of ascorbate and a-tocopherol in sun exposed leaves are consistent with their greater need for antioxidant protection [10].…”
Section: Discussionsupporting
confidence: 64%
“…For both water treatments, seedlings grown at high irradiances showed a higher soluble sugar concentration than seedlings grown under low irradiances. Similar results have been reported by Niinemets [36] in three temperate woody species and by Johnson et al [24] in Fagus sylvatica, but contrast to those presented by Meletiou-Christou et al [30] in four Mediterranean evergreen sclerophylls, which showed no substantial differences on soluble sugars when comparing sun and shade leaves. Changes on water availability through the growing season did not affect either soluble sugar concentration in twoyear-old cork oak seedlings grown outdoors in Portugal, although mean values are higher than ours (between 1.0 and 1.7 mg glucose·cm -2 ), probably related to seedling age [12].…”
Section: (A) (B)contrasting
confidence: 38%
“…Acclimation to different light environments occurs at both whole-plant and leaf levels [24]; leaf acclimation being associated with morphological, anatomical and physiological changes [31]. It is suggested that plants genotipically adapted to open sunny habitats have the ability to acclimate and grow under shaded conditions [42].…”
Section: Introductionmentioning
confidence: 99%
“…However, when both parameters were changed synchronously in the 24°C/500 Pa treatment, productivity was about 150% higher than in the 18°C/ 1,000 Pa treatment, which is substantially more than the added temperature and air humidity effects. In European beech, synergy effects were also observed for the combination of temperature and [CO 2 ] (Saxe and Kerstiens 2005;Bruhn et al 2000), temperature and light (Fotelli et al 2005) as well as for the light/soil fertility interaction (Johnson et al 1997). These results underline the importance of multi-factor studies when attempting to predict the response of trees to climatic changes.…”
Section: Discussionsupporting
confidence: 49%